Testing Industrial-Scale Coral Restoration Techniques: Harvesting and Culturing Wild Coral-Spawn Slicks - Doropoulos, Christopher; Vons, Focco; Elzinga, Jesper; ter Hofstede, Remment; Salee, Kinam; van Koningsveld, Mark; Babcock, Russell C. (Frontiers in Marine Science, 2019)
Accelerating the recovery of marine coastal ecosystems is a global challenge that has been attempted on many systems around the world. Restoration efforts have shown varying levels of success at localised-scales, but developing techniques for large-scale application are still in their nascent stage for many systems. For seagrass meadows and marsh plants, large-scale successes have been realised by distributing seeds from moving boats or planes, respectively. Similarly for coral reefs, the harvesting, developing and releasing of wild coral-spawn slicks to targeted reefs is anticipated to achieve cost-efficient, large-scale restoration of coral communities with low-impact technology. Yet, operational protocols for full-scale application still require development by practitioners. In this study we conducted a field trial to evaluate the actual feasibility of harvesting wild coral-spawn slicks for large-scale restoration activities, incorporating technologies used in oil spill remediation, dredging operations, and land-based aquaculture. Testing the potential for scalability to commercial vessels, our trial focussed on concentrating and collecting wild coral-spawn slicks for culturing until settlement competency using an experimental 50,000 L aquaculture facility built on a tugboat. Five objectives were set and all were achieved successfully, with only one requiring further optimisation. Overall, this restoration approach allows for long-distance translocation of genetically diverse coral assemblages, and may be combined with other larval conditioning techniques that are being developed to increase the resistance to stress and survival of coral recruits. Most importantly, it is fully scalable to produce billions of coral larvae for delivery to target reefs, with negligible impact to source populations.